Hydrogen fuel cell cars - Burlakov, A. V. (ТДАТУ, 2020)
Around the world, there is a growing interest in alternative types of automotive fuels: more economical, environmentally friendly and efficient. They are produced from inexhaustible reserves and generate less emissions into the atmosphere. Developing countries are increasingly abandoning traditional fuels and are striving to switch to a more environmentally friendly one - hydrogen
Keywords: gasoline; diesel fuel; hydrogen